2018
DOI: 10.1044/2017_ajslp-17-0090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Familiarization on Intelligibility of Dysarthric Speech in Older Adults With and Without Hearing Loss

Abstract: This study extends previous findings of improved intelligibility of dysarthria following familiarization to a group of listeners who are critical to consider in listener-targeted remediation, namely, aging caregivers and/or spouses of individuals with dysarthria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…This problem is difficult to solve with training alone. Understanding and being familiar with this characteristic of EL speech in advance may aid in communication with an EL because previous studies (Kim, 2015;Kim & Nanney, 2014;Lansford et al, 2018) showed the benefit of familiarization with dysarthric speech. In addition, the speaker should try to choose the longest word possible, which is the word with the greatest number of morae, provided that it has the correct meaning.…”
Section: Discussionmentioning
confidence: 99%
“…This problem is difficult to solve with training alone. Understanding and being familiar with this characteristic of EL speech in advance may aid in communication with an EL because previous studies (Kim, 2015;Kim & Nanney, 2014;Lansford et al, 2018) showed the benefit of familiarization with dysarthric speech. In addition, the speaker should try to choose the longest word possible, which is the word with the greatest number of morae, provided that it has the correct meaning.…”
Section: Discussionmentioning
confidence: 99%
“…This work has collectively enabled us to reach the following overarching conclusion: Familiarization with dysarthric speech facilitates improvements in a listener's ability to understand the neurologically degraded acoustic signal. To date, the line of investigation following the 2012 review article has chiefly targeted theory; however, robust intelligibility (percent words correct) improvements across the studies, sometimes up to 20%, have been observed (Borrie et al, 2017a(Borrie et al, , 2017bBorrie, McAuliffe, Liss, Kirk, et al, 2012;Lansford et al, 2018). Intelligibility improvements of 5%-12% are considered a guideline for clinically significant change in dysarthria management (Stipancic et al, 2016(Stipancic et al, , 2018Van Nuffelen et al, 2010).…”
Section: Perceptual Learning Of Dysarthric Speechmentioning
confidence: 99%
“…Next, pretest and posttest transcription accuracy scores for each talker were compared to determine if the familiarization experience leads to statistically and clinically Figure 1. Key conclusions from published studies, illustrating significant intelligibility improvements from pretest to posttest for ataxic (Borrie et al, 2017a(Borrie et al, , 2017bLansford et al, 2018), spastic (Borrie & Schäfer, 2015), and hypokinetic dysarthria (Borrie et al, 2018), but not for hyperkinetic dysarthria (Borrie et al, 2018).…”
mentioning
confidence: 95%
“…In response to this critical gap in clinical practice, an alternative approach to intervention, one that targets reduced intelligibility by focusing on the listener rather than the speaker, has been advanced (Liss, 2007). Listener-targeted perceptual training paradigms in which listeners are familiarized with dysarthric speech show promise for improving intelligibility and enhancing communication in dysarthria, without requiring speaker change (e.g., Borrie, McAuliffe, & Liss, 2012;Lansford, Luhrsen, Ingvalson, & Borrie, 2018;Liss, Spitzer, Caviness, & Adler, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation